The Perspectives of English Teachers in Improving Students' Speaking Skills Through Group Discussions - Joko Prayudha.S (English Education Program, Education Faculty, Universitas Nurul Huda, 2023)
Speaking ability is one of the important skills in learning a language. Speaking ability also requires students to be able to produce utterances in the form of speech in the target language. English teachers need to be able to provide fun learning in order to improve students' speaking skills in English. Therefore, this study aims to find out the perspective of English teachers when teaching English through group discussion methods in order to improve the speaking ability of EFL students. The method used in this research is qualitative through a descriptive approach. Data were obtained through field observations when the teacher gave teaching using the group discussion method, then interviews were conducted with two English teachers. Data is analyzed through data reduction, data display, conclusion. The results of the study show that in improving students' speaking skills, the teacher should be able to use learning themes that are appropriate or familiar with everyday habits. In addition, through the group discussion method students can become more confident, brave and can improve their ability to collaborate in solving learning problems.